Vibration serviceability of suspended floor: Full-scale experimental study and assessment. (December 2021) - Lv, Qingfang; Lu, Yujie; Liu, Ye
Abstract: The suspended floor is a relatively new form of floor system in the suspended structure. Owing to the special boundary condition where the whole floor is lifted by cables rather than supported by columns or walls, the suspended floor is flexible and may face the issue of vibration serviceability. In this study, a composite floor lifted by carbon fiber-reinforced polymer (CFRP) cables used for small-scale exhibitions was designed and constructed, and field measurements were conducted to study dynamic characteristics and human-induced vibration serviceability of the suspended floor. The dynamic characteristics test using the natural excitation technique was conducted first, and the fundamental frequency of the floor was determined as 5.08 Hz. Then, the effects of pedestrian number and weight, walking frequency and route, and jumping point and frequency were discussed in the human-induced vibration test. Test results indicated that floor vibration responses increased with the pedestrian number, and increased as the jumping (walking) frequency approached the floor's fundamental frequency. Higher vibration responses were obtained when the human-induced vibration was exerted on positions with less vertical vibration constraints. Vibration serviceability assessment using peak acceleration and root mean square (RMS) acceleration methods neglecting the effect of vibration duration show that the floor can meet the requirement in public places without excitations like walking at high frequency or rhythmic jumping, whereas vibration dose value/ estimated vibration dose value (VDV/eVDV) methods considering vibration duration tend to give a better comment. This study provides a fundamental basis to fill the lack of research on the vibration serviceability of the suspended floor.